2013
DOI: 10.1088/0957-4484/25/2/025704
|View full text |Cite
|
Sign up to set email alerts
|

Patchiness of ion-exchanged mica revealed by DNA binding dynamics at short length scales

Abstract: This is a repository copy of Patchiness of ion-exchanged mica revealed by DNA binding dynamics at short length scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Billingsley et al found that sufficiently short dsDNA molecules (< 800 base pairs, or 260 nm long) deviated from the expected average binding conformation on Ni-mica [205]. These molecules were characterised by surface-equilibrated conformations rather than being kinetically trapped, which provided evidence that the surface distribution of Ni 2+ on the mica was not homogeneous.…”
Section: Adsorption Of Dna To Micamentioning
confidence: 99%
“…Billingsley et al found that sufficiently short dsDNA molecules (< 800 base pairs, or 260 nm long) deviated from the expected average binding conformation on Ni-mica [205]. These molecules were characterised by surface-equilibrated conformations rather than being kinetically trapped, which provided evidence that the surface distribution of Ni 2+ on the mica was not homogeneous.…”
Section: Adsorption Of Dna To Micamentioning
confidence: 99%
“…As a consequence, Mg 2+ only mediates a relatively weak and diffuse adhesion between DNA and the mica surface, allowing DNA molecules to adopt an equilibrated form [22,[31][32][33]. This complex spatial distribution has been rationalized by others [31,33] .…”
Section: Introductionmentioning
confidence: 98%
“…As a consequence, Mg 2+ only mediates a relatively weak and diffuse adhesion between DNA and the mica surface, allowing DNA molecules to adopt an equilibrated form [22,[31][32][33]. This complex spatial distribution has been rationalized by others [31,33] . Previous work has taken advantage of this difference in binding capacities by adjusting the ratio between different monovalent and monovalent-to-divalent ion concentrations in the deposition buffer to alter the surface adhesion of DNA in air [20,34,35].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations